(untitled) (Revista de Letras Norte@mentos, 2017)
It is now 27 years since revised immigration laws brought some 300,000 Japanese-descendant Nikkei Brazilians to Japan for economic opportunities. Brazilian schools were preferred to maintain Portuguese before the 2008 worldwide depression, which also forced many ​Nikkei families to return home. Presently, in the so called ‘Second Generation Resident Brazilians’ age, more ​Nikkei children attend Japanese public schools hoping for higher education. Economic and educational gaps among the youth have widened. Some can attend college and others have become economically and linguistically stateless. This paper explores educational and socio-economic ​ ​issues ​ ​that ​ ​Japanese ​ ​Brazilians ​ ​in​ ​Japan​ ​have ​ ​faced​ ​to​ ​enjoy​ ​full ​ ​citizenship.